IDENTIFIKASI MODEL ANTREAN NON-POISSON (Studi Kasus : Bus Nonpatas Antarkota Antarprovinsi (AKAP) dan Antarkota Dalam Provinsi (AKDP) Lajur Barat Terminal Bus Tirtonadi Surakarta) - Aselina Pratidina Wrediningsih; Sugito Sugito; Alan Prahutama; Arief Rachman Hakim (Department Statistics, Faculty Mathematics and Natural Science, UNIMUS, 2018)
Transportation is an important factor to improve the economic level of an area. If the transportation does great, the economy will grow up. In case of that, Tirtonadi Bus Station always try to provide optimum services to avoid long queue. Queue system on the west lanes nonpatas bus service of Tirtonadi Bus Station (Solo-Yogyakarta, SoloSemarang, Solo-Purwokerto, Solo-Jakarta, and Jalur Pedesaan) will be analyzed using queueing theory. The main goal of this project is to identify the distribution of the model of Non-Poisson and calculate the size of system performance. Primary dataanalysis is made up of equilibrium sample test (steady state) and tested the distribution of the arrivals number and the bus service’s time. Based on the analysis of queueing process, there are non-Poisson queueing models estimated with Triangular, Beta, Weibull, and the models are (G/M/1) : (GD/∞/∞), (G/LOGN/1) : (GD/∞/∞), (G/M/1) : (GD/∞/∞), (G/BETA/1) : (GD/∞/∞), and (G/M/1) : (GD/∞/∞). The size of systemperformance show that line A (Solo-Yogyakarta) have a higher level of service rush than other service lines. Keywords : Queue, Queueing System, Queueing Model, non-Poisson, Tirtonadi Bus Station, Arena.